2015
DOI: 10.1002/pat.3697
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and characterization of controlled drug release carriers based on functionalized amphiphilic block copolymers and super‐paramagnetic iron oxide nanoparticles

Abstract: In this study, synthesis and characterization of magnetic nanocarriers are reported for drug delivery based on the amphiphilic di-block and tri-block copolymers of poly(ethylene glycol) (PEG) and poly(ε-caprolactone) (PCL) with surface modified super-paramagnetite Fe 3 O 4 nanoparticles (magnetic nanoparticles (MNPs)). The synthesized block copolymers (methoxy poly(ethylene glycol) (mPEG)-PCL and PCL-PEG-PCL) were characterized by Fourier transform infrared (FT-IR), 1 H nuclear magnetic resonance (1H NMR), gel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…The mathematical Korsmeyer–Peppas model was used to evaluate the release of QCT. This model has been widely used to characterize drug release mechanisms from spherical nanoparticles . The fitting data (Table ) revealed strong dependence on the pH, suggesting that there is a change in the outer layer of the nanoparticles as function of pH.…”
Section: Resultsmentioning
confidence: 99%
“…The mathematical Korsmeyer–Peppas model was used to evaluate the release of QCT. This model has been widely used to characterize drug release mechanisms from spherical nanoparticles . The fitting data (Table ) revealed strong dependence on the pH, suggesting that there is a change in the outer layer of the nanoparticles as function of pH.…”
Section: Resultsmentioning
confidence: 99%
“…Differential thermogravimetric curve of triblock copolymer showed two weight loss steps due to decomposition of PCL and PEG segments in copolymer (data not shown), which confirms the block copolymer structure. 55 According to the comparison of the T d values of copolymer and homopolymers, thermal stability of PCEC copolymer was higher than that of pure PCL and PEG homopolymers. In a similar study, Wang et al 56 studied PCEC block copolymer and found that increase in T d of the blends was associated with increment in thermal stability.…”
Section: Discussionmentioning
confidence: 98%
“…Their hydrophobic fragments are intended to interact with hydrophobic NPs, while hydrophilic constituents allow for water dispersibility and biocompatibility. Amphiphilic copolymers have been actively utilized for iron oxide NP functionalization, in particular, to develop drug delivery vehicles …”
Section: Introductionmentioning
confidence: 99%
“…Amphiphilic copolymers have been actively utilized for iron oxide NP functionalization, in particular, to develop drug delivery vehicles. [41][42][43][44][45][46] In our preceding work, we studied functionalization of iron oxide NPs synthesized by thermal decomposition of iron oleate, [40] with an alternating copolymer, poly(maleic acid-alt-1-octadecene) (PMAcOD) modified with grafted poly(ethylene glycol) (PEG) tails of different lengths. [47,48] Upon functionalization, oleic acid tails and octadecene units of the copolymer create a hydrophobic bilayer, the properties of which depend on the degree of PEG grafting and the NP size.…”
Section: Introductionmentioning
confidence: 99%